If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15 + -1(5m + 3) = 4 + 4m + -19 Reorder the terms: 15 + -1(3 + 5m) = 4 + 4m + -19 15 + (3 * -1 + 5m * -1) = 4 + 4m + -19 15 + (-3 + -5m) = 4 + 4m + -19 Combine like terms: 15 + -3 = 12 12 + -5m = 4 + 4m + -19 Reorder the terms: 12 + -5m = 4 + -19 + 4m Combine like terms: 4 + -19 = -15 12 + -5m = -15 + 4m Solving 12 + -5m = -15 + 4m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-4m' to each side of the equation. 12 + -5m + -4m = -15 + 4m + -4m Combine like terms: -5m + -4m = -9m 12 + -9m = -15 + 4m + -4m Combine like terms: 4m + -4m = 0 12 + -9m = -15 + 0 12 + -9m = -15 Add '-12' to each side of the equation. 12 + -12 + -9m = -15 + -12 Combine like terms: 12 + -12 = 0 0 + -9m = -15 + -12 -9m = -15 + -12 Combine like terms: -15 + -12 = -27 -9m = -27 Divide each side by '-9'. m = 3 Simplifying m = 3
| 10(s-10)=-205 | | n^2-3n-49=0 | | (x^2/12)^6 | | (^6x^2/12) | | (n+2)(n-5)=39 | | 4=.3x+2x+6 | | 7(4s+5)=91 | | 10+8=78 | | 6(4+x)=54 | | 2(2l+5)=26 | | 8x-10=2x+80 | | 5n+6+7n=18 | | ln(5x-1)=ln(3x+2) | | 3(a-2)=63 | | -x+5+5x=-43 | | .02(.05c+.3)=.03c-.07(.3-.1c) | | p+12-6p=-8-7p | | 25S=3s^2+28 | | (ln(x)-5)*(x+6)=0 | | (U-7)*9=36 | | 5x=(5-7(5-8x))/(8) | | 10(7m-6)=1+9m | | X^2-30+56=-25 | | 39*25= | | 3X/4=×^2/8 | | 3y=16-5y | | -2x+7=x-23 | | 1+2x+3x=16 | | -59-3n=-8(2-5n) | | (E+2)*2=14 | | 2x=(4-5(8-5x))/(7) | | 2x^2+20x=112 |